Thermal efficiency investigation of a ferrofluid-based cylindrical solar collector with a helical pipe receiver under the effect of magnetic field. (October 2021) - Shojaeizadeh, Ehsan; Veysi, Farzad; Habibi, Hossein; Goodarzi, Koorosh; Habibi, Mehrdad
Abstract: This experimental study investigates the advantage of using Mn–Zn Fe2 O4 /water ferrofluid subjected to the effect of a non-uniform magnetic field on the thermal efficiency of a fabricated cylindrical solar collector with a receiver in the shape of the helical pipe. Using ASHRAE Standard, this study has investigated the influence of the nanoparticles volume fraction (0.0–1.0%), the mass flow rate of fluid (0.00415–0.033 kg/s), and the produced non-uniform magnetic field by a set of permanent magnets ( B r = 0.0–1.2 T) on the collector' thermal efficiency. The results show that for the ferrofluid, the overall thermal efficiency of the collector is increased with the volume fraction augmentation. For the case with the flow rate of 0.033 kg/s and the volume fraction of 1.0%, the maximum collector efficiency enhancement compared with water has been 48.54%. The positive effect of applying the magnetic field predominates at lower flow rates and higher volume fractions. In the case with the flow rate of 0.00415 kg/s and the volume fraction of 1.0%, by applying the magnets with B r = 1.2 T, the collector's maximum efficiency is increased by 26.8% compared with that without a magnetic field.